2015
DOI: 10.1002/app.43046
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl chloride film local isometric heat treatment for hidden 3D printing on polymer packaging

Abstract: A method of 3D embossed printing is proposed where both point and line images can be printed on rigid polyvinyl chloride (PVC) shrink films without any consumables, such as paints, primers, dampening solutions, or washes. Embossed lettering and symbols on packaging are intended for people with poor vision, but capable of tactile marking recognition and reading Braille. This 3D printing is based on reversible deformation and stress relaxation in anisotropic glassy polymers by local isometric heat treatment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…9 Moreover, heating mechanically unconstrained film for the relief to appear resulted in warped and unsightly embossed imprint. To maintain planarity of prints or their cylindrical shape, corresponding to the shape of the packaging, which is particularly important for labels, heat shrinking is proposed to be carried out directly on the product or the rigid material substrate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…9 Moreover, heating mechanically unconstrained film for the relief to appear resulted in warped and unsightly embossed imprint. To maintain planarity of prints or their cylindrical shape, corresponding to the shape of the packaging, which is particularly important for labels, heat shrinking is proposed to be carried out directly on the product or the rigid material substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that shrinking of PVC glassy polymer films, heated to glass transition temperature and 20-30 8C above the glass transition temperature, leads to a two-stage compressive stresses increase. 10 The first stress rise is due to shrinkage and stress relaxation during cooling of stressed films in manufacturing. The second stage is a result of stressed films cooling under isometric conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations